Ecogeografia e desempenho agronômico de Lippia insignis Moldenke em três sistemas de cultivo - Sales, Raul Pinho (2020)
Among the genera of the Verbenaceae family, Lippia is the second largest, with about 200 species. It has a strong characteristic, a strong aroma, and in the flowering period it has a very attractive visual aspect and its species arouse interest for having essential oils with rich biological activity. Lippia insignis Moldenke is a medicinal plant characterized as a shrub that can reach 3 m in height, branched and for having strongly aromatic oval leaves. The species is at risk of extinction due to anthropic impacts related to irrational exploitation of natural resources of the region where it is endemic, in the Chapada Diamantina’s rock fields. In this ways, this work’s objective was evaluating the ecogeography and the agronomic performance of Lippia insignis Moldenke in three cultivation systems. An ecogeographic survey was carried out in 20 points of natural occurrence of the species, through the database of biological collections SpeciesLink, distributed in 15 cities in the state of Bahia. The agronomic experiment was carried out at Fazenda Morrinhos, based in the municipality of Tanquinho - BA. Thes plants, propagated by cuttings, were grown in consortium with forage palm, in an agroforestry system and in monoculture, with 40 experimental units divided into plots subdivided by treatment. After seven months of planting, evaluations of growth parameters, content and essential oil yield of the different treatments were carried out. Results obtained demonstrate that the species occurs predominantly in the Caatinga biome, with some populations found in the Cerrado and Atlantic Forest. The species occurs between altitudes of 53 to 1376 meters, with precipitation varying between 465 and 2057 millimeters and the average temperature between 17.1ºC and 26.7°C. Results of the evaluation on agronomic performance indicate that the species can be cultivated in all the crop systems analyzed in this work, mainly due to the fact that no significant differences were observed for essential oil content and oil yield per plant. Due to the socio- environmental benefits, biodiversity systems must be prioritized.